An approach for Embedding Elliptic Curve in Fractal Based Digital Signature Scheme - Ojha, D. B.; Shree, Ms.; Dwivedi, A.; Mishra, A. (Journal of Scientific Research, 2010)
We established a new approach for cryptographic digital signature scheme based on Mandelbrot and Julia fractal sets. We have embedded the features of ECC (elliptic curve cryptography) to the digital signature scheme based on Mandelbrot and Julia fractal sets. We offered a digital signature that has advantages of both the fractal based digital signature as well as of elliptic curve digital signature. Keywords: Fractal; ECC; Digital signature. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.4694 J. Sci. Res. 3 (1), 75-79 (2011)